اختبار فعالية بعض المخصبات (العضوية والحيوية) في تحسين الخصائص الإنباتية للبذور ونمو شتول الفليفلة Capsicum annum L. (Latakia University Journal -Biological Sciences Series, 2017)
هدف البحث الحالي إلى دراسة بعض المخصبات العضوية والحيوية في الخصائص الإنباتية ونمو شتول الفليفلة. استخدم صنف الفليفلة "قرن الغزال" ، اختبر مركبان تجاريان عضوي (هيوبست Hubest ) وآخر حيوي (EM1). تضمنت الدراسة تجربتين ، الأولى بهدف دراسة أثر المخصبات في الخصائص الإنباتية لبذور الفليفلة ، زرعت البذور في أطباق بتري وفي أحواض بلاستيكية مملوءة بالبيتموس.بينما هدفت التجربة الثانية إلى دراسة أثر المخصبات في نمو شتول الفليفلة . إذ جرى إعداد الشتول في صواني من الستريبور بأبعاد 5×5 سم مملوءة بالبيتموس داخل نفق بلاستيكي غير مدفأ.أظهرت النتائج أن نقع البذور في المخصبات ( العضوية والحيوية) المستخدمة أدى إلى تنشيط الإنبات وزيادة قوة البذور، وكان هذا الدور أكثر وضوحاً عند النقع في محلول المركب الحيوي. إذ أظهرت البذور المعاملة بهذا المركب تفوقاً معنوياً في الصفات المدروسة .كما أظهرت الدراسة أن معاملة الشتول بالمخصبات أعطت زيادةً ملحوظة في معدل نمو الشتول ، تجلى في طول الشتلة ، وأعداد الأوراق ومساحة سطحها التمثيلي وكذلك في الوزن الرطب والجاف للمجموع الخضري مع تفوق معنوي واضح للشتول المعاملة بالمركب الحيوي. The aim of this study was to test the effeciency of some organic and bio fertilizers in improving the seeds germination and transplants growth of pepper Capsicum annum L. local variaty" Qorn Algazal":by using two commercial compounds; organic (Hubest) and one bio (EMI) fertilizers. Two experiments were used; the aim of the first was to study the effect of these fertilizers on germination of seeds in Petri dishes and plastic peatmoss peds. Whereas the aim of the second experiment was to evaluate the effect of the fertilizers on the pepper transplants growth that prepared in the 5 * 5 Striopor peatmoss plates placed in un warmed plastic tunnel. The results showed that the soaking of pepper seeds in the tested fertilizers, provoked and the germination increased the seeds, vigor, with a significant performance of the bio fertilizer.The results also showed that the treated transplants with the tested fertilizers gave an increase of the transplants growth ratio (the height, leaves number and foliar surface area, the dry and wet weight) with a significance superiority of the bio fertilizer.